Advokat sebagai Officium Nobile Berasarkan Undang-Undang No. 18 Tahun 2003 tentang Advokat - Amalia Nurzannah; Amanda Fildzah Sagala; Fauziah Lubis (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
The Advocate profession is an honorable profession (officium nobile) that is subject to a code of ethics by the provisions. The position of an Advocate that is equal to other law enforcers makes Advocates have an important role in the legal order in Indonesia. Seeking truth and justice based on morality, integrity, and knowledge. This study aims to find out how the role of an Advocate as officium nobile is based on Law No. 18 concerning Advocates. By using research methods with a normative juridical approach concerning legal norms and relevant literature. So that the result is that Advocates are referred to as noble professions (officium nobile) because they carry out the task of helping provide justice and enhancing human dignity. The naming of an Advocate as officium nobile is because of the aspect of trust that is carried out to fight for people's rights. As a noble profession, advocates are required to be able to assist free of charge in helping people seek truth and justice. Keywords: Officium Nobile, Justice, Law Enforcement